2019
DOI: 10.15252/embr.201948068
|View full text |Cite
|
Sign up to set email alerts
|

Differential contribution of steady‐state RNA and active transcription in chromatin organization

Abstract: Nuclear RNA and the act of transcription have been implicated in nuclear organization. However, their global contribution to shaping fundamental features of higher‐order chromatin organization such as topologically associated domains (TADs) and genomic compartments remains unclear. To investigate these questions, we perform genome‐wide chromatin conformation capture (Hi‐C) analysis in the presence and absence of RNase before and after crosslinking, or a transcriptional inhibitor. TAD boundaries are largely una… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 84 publications
4
70
0
Order By: Relevance
“…Previous studies have shown that global disruption of RNA by RNase A leads to disruption of HP1 localization at chromocenters 91 . However, RNAse A is not specific and can impact several structures in the nucleus, including nucleoli 93 . Because major and minor satellite-derived ncRNAs localize exclusively within centromere-proximal structures, we hypothesized that these ncRNAs might be important for HP1 localization.…”
Section: Satellite-derived Ncrnas Organize Hp1 Localization At Inter-mentioning
confidence: 99%
“…Previous studies have shown that global disruption of RNA by RNase A leads to disruption of HP1 localization at chromocenters 91 . However, RNAse A is not specific and can impact several structures in the nucleus, including nucleoli 93 . Because major and minor satellite-derived ncRNAs localize exclusively within centromere-proximal structures, we hypothesized that these ncRNAs might be important for HP1 localization.…”
Section: Satellite-derived Ncrnas Organize Hp1 Localization At Inter-mentioning
confidence: 99%
“…Previous reports have proposed that actively transcribed genes may play such a role. First, Transcriptional Start Sites (TSSs) of housekeeping genes are enriched at TAD borders (8,35) and, second, the act of transcription can affect 3D genome structure independently of CTCF (36)(37)(38). However, whether an actively transcribed gene can behave as a boundary, in a similar manner to a CTCF element, has not been previously tested in mammalian systems.…”
Section: Gene Expression Throughout Development and Differentiation Imentioning
confidence: 99%
“…D) Cytological visualization of NPM1 under indicated conditions. nization such as topologically associated domains (TADs) remain unaffected, a subtle change in long-range interactions within heterochromatic, gene-poor, and silent genomic compartments is observed upon RNA depletion (Barutcu et al, 2019). However, the low resolution of both cytology and Hi-C methods limits their use in deciphering the involvement of RNA in chromatin structure.…”
Section: Introductionmentioning
confidence: 99%